Preparation and properties of a novel waterborne epoxy resin modified emulsified asphalt. (31st March 2023) - Shi, Shuang; Zang, Dongdong; Chen, Xiang; Ma, Tao; Gu, Linhao; Xu, Degen; Liu, Jie
Highlights: Waterborne epoxy resins reduce VOC emissions, in line with today's environmentally friendly material concepts. Grafting copolymerization improves the bond strength of waterborne epoxy, with which can be no loss of epoxy groups. The properties of waterproof bonding layer were investigated, which provided guidance for engineering application. Abstract: Waterborne epoxy resin is one alternative to enhance bond strength and storage stability for waterproof adhesive layer. Grafting copolymerization is selected in this paper as one experimental case to investigate its properties and also a feasible innovative preparation. The impact of the preparation process on the grafting rate of acrylic monomer was also considered. Moreover, the effect of the amount of acrylic monomer on the centrifugation stability and particle size of the emulsions was studied, where the infrared spectra were used to verify that hydrophilic groups incorporated into the main body of the aqueous epoxy resin. Main tests for modified emulsified asphalt are designed as it pulls out strength and storage stability under various temperature. The results showed that the highest grafting rate of acrylic monomer was achieved at the grafting temperature of 110℃ and grafting time of 2 h. The centrifugal stability of the emulsion was optimum when the amount of acrylic monomer reached 30%, at this time, the median particle size of the emulsion was 160 nm; the infrared spectrum showed that the epoxy resin main chain successfully introduced hydrophilic group (–COOH) at 1720 cm −1 . When the amount of water-borne epoxy resin exceeded 40%, the pull-out strength of waterborne epoxy resin modified emulsified asphalt increased significantly at 25℃ and 40℃, and its storage stability was optimized when the content of waterborne epoxy resin reached 50%. The waterproof adhesive layer material prepared in this study has potential application value for improving the quality of bridge deck pavement and construction projects.